HYPERTENSIVE DISORDERS IN ECUADORIAN PREGNANT WOMEN 2010-2014 - Nader, Jorge Daher; López, Alida Bella Vallejo (International Journal of Research -GRANTHAALAYAH, 2018)
Hypertensive disorders are serious illnesses that manifest in different forms and can be fatal. This study aims to demonstrate the impact of hypertensive disorders in pregnancy and the difficulty in public health by limiting timely identification and diagnosis of these diseases. The completion of this study will help to obtain the information necessary to understand the manifestations of hypertensive disorders in the Maternity Enrique C. Sotomayor on a study period of 5 years. The study will be beneficial for the pregnant patient and the institution as valuable information is obtained to analyze the behavior of these disorders and to perform protocol of information for professionals in the institution. Among the results obtained during five years in the institution were 13.066 patients diagnosed with hypertensive disorders, severe preeclampsia being the most common hypertensive stage with 77.3%. There is a significant increase of the disease with the passing of the years, and in 2013 was the second cause of c-sections for the first time in patients with seven antenatal control program. Death by hypertension in pregnancy was presented in three occasions. With regard to the damages in the fetus birth weight is frequently altered, reporting in 2014-571 newborns diagnosed with growth retardation and fetal malnutrition.